Gaming the Metrics : Misconduct and Manipulation in Academic Research - Biagioli, Mario; Lippman, Alexandra; Biagioli, Mario; Lippman, Alexandra (Cambridge The MIT Press, 2020)
How the increasing reliance on metrics to evaluate scholarly publications has produced new forms of academic fraud and misconduct. The traditional academic imperative to (3z(Bpublish or perish(3y (Bis increasingly coupled with the newer necessity of (3z(Bimpact or perish(3y$1 (Bthe requirement that a publication have (3z(Bimpact,(3y (Bas measured by a variety of metrics, including citations, views, and downloads. Gaming the Metrics examines how the increasing reliance on metrics to evaluate scholarly publications has produced radically new forms of academic fraud and misconduct. The contributors show that the metrics-based (3z(Baudit culture(3y (Bhas changed the ecology of research, fostering the gaming and manipulation of quantitative indicators, which lead to the invention of such novel forms of misconduct as citation rings and variously rigged peer reviews. The chapters, written by both scholars and those in the trenches of academic publication, provide a map of academic fraud and misconduct today. They consider such topics as the shortcomings of metrics, the gaming of impact factors, the emergence of so-called predatory journals, the (3z(Bsalami slicing(3y (Bof scientific findings, the rigging of global university rankings, and the creation of new watchdogs and forensic practices.s
English
Keywords: Universities; Examinations & assessment; Coding theory & cryptology; gaming; metric; citation; misconduct; manipulation; academic research; gaming metrics; peer review; impact factor; fraud; fake; predatory publishing; impact assessment; citation index; open access; journal impact factor; JIF; scholarly communication; research evaluation; publication pressure; publish or perish; education policy; spam; computer-generated articles; altmetric; data quality; performance indicators